ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK REKLAME DAN PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH KOTA MADIUN (STUDI PADA BADAN PENDAPATAN DAERAH KOTA MADIUN TAHUN 2020-2024). - Hery Hermawan; Henry Windrianto Darmoko; Fatchur Rochman (JAMER : Jurnal Akuntansi Merdeka, 2026)
This study aims firstly to test and prove the extent to which the effectiveness of Advertising Tax and Entertainment Tax revenues affects the Original Regional Income of Madiun City in 2020-2024; secondly, to test and prove the extent to which the contribution of Advertising Tax and Entertainment Tax revenues affects the Original Regional Income of Madiun City in 2020-2024. The data used in this study is quantitative data in the form of Budget Realization Report (LRA). The results of the study indicate that the level of effectiveness of advertising tax revenue is in the less effective category. From the t-test it can be seen that the effectiveness of Advertising Tax individually (partially) affects the Realization of Original Regional Income. The effectiveness of entertainment tax for five years also shows the less effective category. From the results of the t-test, it shows that the effectiveness of Entertainment Tax individually (partially) affects the Realization of Original Regional Income. The contribution of advertising tax and entertainment tax to PAD is still very low.